Pemanfaatan Rebusan Daun Sirih Merah (Piper crocatum) Dalam Menurunkan Tingkat Kejadian Mastitis Berdasarkann Uji CMT dan SCC - Razan Harastha Sjuhada; Puguh Surjowardojo; Endang Setyowati (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
The red betel leaves (Piper crocatum) known as herbal antiseptic that contain many substances like essential oil, flavonoid, saponin, and tannin. The red betel leaves can be use to replace chemical antiseptic and more safe to use for teat dipping for dairy cow. The purpose of this research was to determine the effect of teat dipping with red betel leaves decoction to decrease subclinical mastitis level and somatic cell based on CMT and SCC. The method in this research was experiment with Randomize Block Design with 3 treatments and 5 replications. The data analyzed with Analysis of Variance (ANOVA), if there were significant effects it would be continue by Duncan’s Multiple Range Test (DMRT). The results showed that teat dipping with red betel leaves decoction had a significant different (P<0.05) to decrease mastitis level. Teat dipping with red betel leaves decoction 20% concentration could decrease mastitis level up to 30%. Teat dipping with red betel leaves decoction had a significant difference (P<0.05) to decrease the amount of somatic cell too. Teat dipping with red betel leaves stew 20% concentration could decrease the amount of somatic cell up to 1.98% or 0.12CFU/ml. The conclusion that teat dipping with red betel leaves decoction 20% was the best concentration and gave the best results to decrease mastitis level and somatic cell.